Electoral college reform : challenges and possibilities - Bugh, Gary. (Election law, politics, and theory., 2010)
Why hasn't the United States reformed the Electoral College system, and how can it best do so? To address these questions, Electoral College Reform: Challenges and Possibilities brings together new essays by law professors and political scientists examining the reasons for reform, the issues surrounding a Constitutional amendment, the effect of the Electoral College on political campaigns and government policymaking, and the possibilities for extra-Constitutional avenues to change, including the courts and the state legislatures.